Assessing the information content of the statement of internal control of selected second board Malaysian public listed companies: a qualitative approach / Masetah Ahmad Tarmizi and Normah Omar - Ahmad Tarmizi, Masetah; Omar, Normah (Universiti Teknologi MARA Cawangan Selangor, 2012)
In the Revamped Bursa Malaysia Listing Requirement 2001, all public listed companies are required to include a statement of internal control (SIC) in their corporate annual reports. SIC is an important statement to highlight to the stakeholders, the steps taken by the company to manage and control its business risks. To manage risk properly, appropriate risk assessments and evaluations are needed. Once risks have been identified, the company needs to implement an appropriate control system to manage and control these risks regularly. Nevertheless, all relevant processes and procedures on internal control system must be transparently described and illustrated by the proposed SIC. This paper highlights the need to develop an assessment instrument to evaluate the information content of the SIC. An evaluation of the statement of internal control of selected second board counters portrays a fairly unfavorable scenario. In general, these companies do not provide good information content on their internal control system. Most of the companies under review give minimum information to the stakeholders. The low score of the SIC is primarily due to the insufficient monitoring and enforcement by the regulatory bodies in Malaysia. In moving forward, this study proposes the use of a self-assessment SIC checklist. Companies must take it upon themselves to be transparent and comply with the various requirements enforced upon them. In other words, they must take care of themselves.